Vliyanie ω-3-polinenasyshchennykh zhirnykh kislot na svobodnoradikal'nye protsessy i strukturnoe sostoyanie membran eritrotsitov u patsientov s metabolicheskim sindromom (Ожирение и метаболизм, 2010)
This article presents data on tissue sensitivity to insulin, type of change in antioxidant-prooxidant system and membrane structure of erythrocytes in 30 patients from 20 to 58 years of age with metabolic syndrome who received a preparation of ω-3 polyunsaturated fatty acids. After 3 months of treatment with omacor we revealed the increase in the tissue insulin sensitivity, lowering of the free radical activity, normalization of antioxidant enzyme activity and erythrocytes membranes stabilization.